The Gingivitis and enamel defect among students of Dentistry College in Babylon, Iraq - Hussain Wais, Zahraa; Salman, Omaima Lateef; AL Khafaji, Sarah Y.; Wais, Alaa Mohammed Hussein (Journal of Pakistan Association of Dermatologists, 2023)
Background Gingivitis is one of the commonest oral diseases after dental caries occur in many countries. Dental plaque is main cause of gingival disease. Another oral disease that measured in this study is enamel defect. Objectives The aim of this study was to measure the oral hygiene problem (dental plaque and measure the severity and prevalence of gingival disease) and enamel defects among 22-23 years old students of dentistry college in Babylon Iraq. Methods A representative sample included in this study consisted of 300 students, they were selected randomly. Dental plaque was measured using Silness and Loe (1964) plaque index. The gingival health condition was measured using Loe and Silness (1963) gingival index, while enamel anomalies was measured following the criteria of WHO. Results The mean value of plaque index of total sample, for females was 1.11 and male is 1.47 the mean value of gingival index of female was 1.027 and male was 1.30 with statistically, no significant difference (P value > 0.05), the enamel defect prevalence was 29%. The most prevalent type of enamel anomalies was demarcated opacity (12%) followed by diffused opacity (10%). Conclusions Demarcated opacity was common type of enamel defects. The demarcated opacity is a defect include change in the translucency and has a clear boundary with the adjacent normal enamel. The color may be white, cream, brown or yellow.